Studi Kualitas Hidup Pekerja Komuter Pengguna KRL Commuter line dan Busway Transjakarta dari Bogor ke Jakarta - David Kusmawan; Susilowati, Indri Hapsari (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2020)
Background: Many studies have concluded that commuting activities have an impact on the quality of life of commuters on both physical, mental / psychological, health, and social / environmental aspects of commuting. The purpose of this study was to determine the quality of life of commuting workers of busway Transjakartaand train commuter linemodes of transportation from Bogor to Jakarta and what factors which influenced it. Methods:This study was conducted using cross sectional design with WHO Quality of Life BREF questionnaire. Analysis with univariate and bivariate with Chi square. Results: The result showed the respondents had used train commuter line for ≥ 4 years (50.6%) while busway Transjakartauser workers <4 years were 52.5% with frequency ten times a week for train commuter line(72.4%) The quality of life of user commuter line and busway Transjakara is categorized by percentage of 57.1% and 70%. Conclusion:The psychological and environmental domains have the highest scores on both mode transportation while the physical domain has the lowest score. Bivariate analysis revealed the quality of life in train commuter line workers affected by income and psychological conditions. While the worker busway Transjakarta usersaffected by type of work Keywords: Quality of Life, WHOQOL BREF, Worker Commuter, Busway Transjakarta, Train Commuter line